Tirakat Puasa Bilaruh sebagai Upaya Mengembangkan ESQ (Emotional Spiritual Question) Santri Pondok Pesantren Lirboyo HM Putri Al Mahrusiyah - Nur Hijja Fiddari; Moh. Turmudi (Indonesian Journal of Humanities and Social Sciences, 2020)
This article describes how the concept of Tirakat Tirakat fasting from the perspective of students and the form of implementing Tirakat Tirakat on fasting bilaruh as an effort to develop the ESQ (Emotional Spiritual Question) for Santri. Tirakat on fasting bilaruh is a form of concern that aims to get closer to Allah. Tirakat culture is a form of acculturation of Islam with the local culture. This research uses qualitative research with a phenomenological approach. Data collection techniques using in-depth interviews, observation, and documentation. The results reveal that the santri perspectives tirakat fasting are a form of tirakat or concerning behavior as well as the development of the students' ESQ. In addition, this fast becomes a bridge to make it easier to understand and memorize lessons. However, not all students who carry out this fast have a high ESQ, but fasting that is done istiqamah and with the right intention can develop the ESQ of the students. in its implementation, the tirakat fasting bilaruh has several provisions that are different from other fasts both in the time and in the several aurad that are read.